Odpowiedzi

2010-02-19T14:12:10+01:00
11
c) 3(a+2b-3c) + 7(2a-4b+5c)-5(-3a-4b-5c) = 3a+6b-9c+14a-28b+35c+15a+20b+25c=32a+54b+46
12
c)10p+15r+20s= 5(2p+3r+4s)
d)8e+12f+20g+24= 4(2e+3f+5g+6)
g)-6u+12w-9y+6= -3(2u-4w+3y-2)
h)-9+18h-27b+36c= 9(-1+2h-3b+4c)

uf , proszę o naj :)
2010-02-19T14:23:57+01:00
A)36a-2a+c
b)-49x-118y+81z
c)-17b+22c
WYŁĄCZ CZYNNIK PRZED NAWIAS
A)6x+3y=3(2x+y)
B)12a+9b+15c=3(4a+3b+5c)
C)10p+15r+20s=5(2p+3r+4s)
D)8e+12f+20g+24=4(2e+3f+5g+6)
E)-6y-9x-3=3(-2y-3x-1)
F)5x-15y-20z=5(x-3y-4z)
G)-6u+12w-9y+6=3(-2u+4w-3y+2)
H)-9+18a-27b+36c=-9(1+2a+3b+4c)
I)..............
J)-3,5a+10,5ab-17,5ac=-3,5a(3b+5c)